Spirulina does not decrease muscle damage nor oxdidative stress in cycling athletes with adequate nutritional status - Franca, G. A. M.; Silva, A. S.; Costa, M. J. C.; Moura Junior, J. S.; Nobrega, T. K. S.; Goncalves, M. C. R.; Asciutti, l. S. R. (Biology of Sport, 2010)
The objective of this study was to assess the effect of Spirulina maxima on oxidative stress and muscle damage in cycling athletes subjected to high volume and intensity of training. Eighteen male athletes were randomly divided into an experimental group (n=11) with age 27.8±3.5 and placebo (n=7) with age 34.3±2.3 in a double-blind fashion. They carried out a protocol of Spirulina dietary supplementation (7.5 g/day) of placebo for four weeks and maintained their trainings during this period. A nutritional anamnesis was performed and blood tests were done to determine pre and post levels of creatine kinase (CK), lactic dehydrogenase (LHD), superoxide dismutase (SOD) and malondialdehyde (MDA). The supplemented and placebo groups performed the same volume training, has adequate macronutrients and antioxidant vitamins ingestion before study, as well as initial CK, LDH, SOD and MDA levels. Supplementation did not promote a significant alteration in CK levels on supplemented group (158.4±16.3 for 140.0±16.6 U/l, p>0.05), LDH (420±13.2 for 394.9±27.9 UI/l, p>0.05), MDA (2.8±0.2 for 2.9±0.4 nmol/ml, p>0.05), nor an increase in the SOD (7.3±0.6 for 7.0±0.6 U/mg Hb, p>0.05). We conclude that administration of Spirulina does not interfere in the magnitude of muscle damage nor in antioxidant status of cycling athletes that practice intense training.